AN ANALYSIS OF INFORMATION SYSTEMS RESEARCHER AND COLLABORATION RANKINGS. Issue 3 (3rd July 2021) - O'Leary, Daniel E.
ABSTRACT: This paper investigates a career database with a ranking of researchers, over the time period 1960–2019 based on a composite measure of Scopus citations, using the H-index, H-M-index and other metrics. This paper drills down on those researchers for which information systems is characterized as their primary focus. In so doing we investigate issues, related to collaboration and other concerns. In addition, the paper compares that set of rankings to a set of rankings for information systems researchers based on Google Scholar H-index, which allows us to compare Scopus H-index, Scopus H-M index and other analytics for those researchers.